Effects of ore-rock falling velocity on the stored materials and the force on the shaft wall in a vertical orepass - Yang, Yu-jiang; Deng, Zhe; Lu, Zeng-xiang (Mechanics of advanced materials and structures, 2023)
The fall of the ore-rock will have an impact-tamping effect on the materials stored in a vertical orepass and affect the flow characteristics of the storage materials and the stress state of the orepass wall, which may cause the blockage of the orepass and the deformation and damage of the shaft wall. The research adopts a numerical simulation method forming a cylindrical orepass wall and creating the storage materials in the orepass with randomly distributed spheres and irregular polyhedrons, analyzes the change law of the impact force on the shaft wall and the material in the orepass, and the change law of the voidage of the storage materials under the conditions of different initial ore-rock falling rates. The results indicate that (1) the impact of falling ore-rock on the shaft wall is concentrated in some range below the material surface, and the impact of the shaft wall around the material surface is the most obvious; (2) the materials' voidage decreases with the increase of the ore-rock falling rate, and its variation is most apparent in part close to the material surface, but the overall voidage changes slightly; (3) the internal force chain system is stable after the accumulation of materials in the orepass is formed, the impact process of the ore-rock falling just affects the force chain with a length of fewer than four blocks and has no noticeable effect on the skeleton structure composed of longer force chains at the lower part in the orepass.